Assess impact of oral health on the psychological health of adults - Wedad Tulihan Alonazi; Fatimah Abdullah Saleh Alshaikhi; Sulafa Aljeelani Fal; Abdulrahman Saeed Alghamdi; Kholoud Atiah Alghamdi; Hawra Al-Mubarak; Alhazmi Sulaiman Abdulaziz S; Hussain Ahmed Alshawaf; Hassan Alwayil; Hind Husaain Almohammed; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: As the global population ages, adults over 65 are increasingly retaining natural teeth, highlighting the need for tailored oral healthcare to meet the unique needs of older adults. Oral health plays a crucial role in the physical, emotional, and social well-being of this population, as poor oral health can exacerbate conditions like diabetes, cardiovascular disease, and nutritional deficits, which can impact self-confidence, social interaction, and potentially lead to social isolation and decreased well-being. Methods: This study utilized data from a longitudinal study on healthy aging, focusing on individuals aged 79 and older who live independently. A total of 201 participants were assessed through structured, in-home interviews and self-completed questionnaires. Variables collected included demographics, general health, social activity, and detailed oral health metrics such as dentition, dental pain, denture use, and dental appearance concerns. Psychological well-being (PW) and depressive symptoms were measured using validated scales, including the Philadelphia Geriatric Center Affect Scale. Data were analyzed with Chi-square, one-way ANOVA, and Pearson’s correlation tests, followed by multivariate linear regression to identify predictors of well-being. Results: Participants, with an average age of 83.9 years, exhibited varied dental statuses, with 65.1% partially dentate and 31.3% edentulous. Positive affect scores were linked to minimal dental appearance concerns, meal enjoyment, social activity, and general health. Negative affect and depressive symptoms were more frequent among participants with dental appearance concerns, frequent dental issues, or who avoided specific foods due to oral health problems. Dental appearance, general health, social activity, and physical limitations were significant predictors of psychological well-being and depressive symptoms, explaining a substantial portion of score variance in each outcome. Conclusion: This study underscores the significant role of oral health in the well-being of older adults, particularly the influence of dental appearance and function on psychological health. The findings support the need for targeted oral health programs and policies to enhance quality of life and mental well-being in the aging population. Future research should integrate longitudinal designs and clinical assessments to further clarify the relationship between oral health and well-being in older adults.